Housing Preference and Choice of Nigerians: Evidence from the Organised Private Sector Housing - Adegoke, Samson Akinbamide Omobayo (Advances in Social Sciences Research Journal, 2022)
The decline of housing as a political priority despite growing demand has made housing choice decision more difficult. This study is an examination of the revealed preference of beneficiaries of organized private sector housing delivery in Nigeria. The study relied on data collected from sampled estates from two (2) states in each of the six geo – political zones of Nigeria. These are flats, bungalows, semi – detached and detached houses. In all, about 58% of all beneficiaries choose flats about 31% choose bungalows 7% choose semi – detached houses and only about 4% of all the beneficiaries choose detached houses. The findings from this study showed that about 89% of all beneficiaries choose flats and bungalows. The policy implication of the preponderance of flat and bungalow in the housing choice of beneficiaries is that they are the popular, acceptable and affordable typologies of Nigerians. Therefore, these types of houses should be given priority in funding by National Housing Trust Fund (NHTF).